Self-association of MreC as a regulatory signal in bacterial cell wall elongation - Alexandre Martins; Carlos Contreras-Martel; Manon Janet-Maitre; Mayara M. Miyachiro; Leandro F. Estrozi; Daniel Maragno Trindade; Caíque C. Malospirito; Fernanda Rodrigues-Costa; Lionel Imbert; Viviana Job; Guy Schoehn; Ina Attrée; et al. (Nature Communications, 2021)
MreC is a membrane-associated protein that modulates the activity of the elongasome, a protein complex that controls cell wall formation in rod-shaped bacteria. Here, the authors use electron cryo-microscopy and X-ray crystallography to determine the structure of a self-associated form of MreC in atomic detail.